Heavy menstrual bleeding and iron-deficiency anemia in physically active women: dietary strategies, screening, and referral red flags – a narrative review - Lohin, Mariia-Khrystyna; Karol , Michał; Koseska, Kamila; Borowicz, Jan; Górecki , Bartosz; Kloch, Kinga; Romaniuk , Patryk; Strawińska, Aleksandra; Bednarczyk, Małgorzata (Quality in Sport, 2026)
Purpose: Heavy menstrual bleeding (HMB) is common in reproductive-age women and may be underreported in sport, where fatigue is often attributed to training load, stress, or low energy availability. This narrative review summarizes evidence on HMB coexisting with iron deficiency (ID) and iron-deficiency anemia (IDA) in physically active women and translates it into practical screening, nutrition, and referral guidance. Materials and Methods: FIGO AUB (PALM–COEIN) and NICE guidance were integrated with sports-medicine evidence on exercise-related iron stress and post-exercise hepcidin regulation. Results: HMB can deplete iron stores before anemia is detected on routine blood counts. In athletes, increased iron demand and losses and transient hepcidin elevations may further reduce absorption and functional iron availability; serial ferritin assessment is often more informative than a single test. Conclusions: An integrated pathway - routine screening questions, appropriate laboratory testing, individualized nutrition, monitored supplementation when indicated, and timely gynecology/hematology referral when red features are present - may improve health protection and training continuity.